2021
DOI: 10.3389/fpsyt.2021.620037
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Change During Inpatient CBASP Treatment: Focus on Group Therapy

Abstract: Background: The Cognitive Behavioral Analysis System of Psychotherapy (CBASP) has been tailored specifically to the demands of patients with persistent depressive disorder (PDD). According to the CBASP model, PDD patients are supposed to live perceptually disconnected from their social environment, which consequently maintains depression. While initially developed as an individual treatment modality, the adaptation for group therapy yields an important interpersonal space. However, little is known about the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…This corresponds to the results of previous studies, which also reported no direct benefit of resource-oriented interventions on depression (Bolier et al, 2013; Teismann et al, 2011). Nevertheless, other studies have demonstrated an antidepressant effect of group therapies with and without a resource-activating focus (Dinger et al, 2020; Feng et al, 2012; Guhn et al, 2021; Huntley et al, 2012; Liwowsky et al, 2014; Okumura & Ichikura, 2014; Steinert et al, 2017; Troesken & Renneberg, 2019; Victor et al, 2016; Weiner et al, 2018). However, these studies did not always examine samples consisting exclusively of patients with affective disorders or did not include control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the results of previous studies, which also reported no direct benefit of resource-oriented interventions on depression (Bolier et al, 2013; Teismann et al, 2011). Nevertheless, other studies have demonstrated an antidepressant effect of group therapies with and without a resource-activating focus (Dinger et al, 2020; Feng et al, 2012; Guhn et al, 2021; Huntley et al, 2012; Liwowsky et al, 2014; Okumura & Ichikura, 2014; Steinert et al, 2017; Troesken & Renneberg, 2019; Victor et al, 2016; Weiner et al, 2018). However, these studies did not always examine samples consisting exclusively of patients with affective disorders or did not include control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aim of the present study was to conduct a randomized, controlled investigation of a newly developed group therapy for resource activation (GTRA) for patients with affective disorders. The group setting was viewed as particularly suitable for resource activation because group therapies have proven to be effective for the treatment of inpatients with depression (Dinger et al, 2020; Guhn et al, 2021; Liwowsky et al, 2014; Weiner et al, 2018), achieve comparable effect sizes to individual therapies (Cuijpers et al, 2006; McDermut et al, 2001), and offer the advantage that several patients can benefit from therapeutic interventions at the same time. Moreover, group interventions for supporting interactive and pleasurable experiences should specifically contribute to the satisfaction of basic needs (especially bonding and pleasure), which promotes the activation of resources (Grawe & Grawe-Gerber, 1999).…”
mentioning
confidence: 99%
“…Similar findings were obtained in a previous study, which found that after receiving psychotherapy intervention, adolescents with depressive disorders reported higher psychological well-being and self-esteem than those in the control groups [12]. Research in Iran reveals group psychotherapy significantly increases the level of hope in patients with major depressive disorder [13].Qualitative research conducted by Guhn et al, showed that respondents reported five main benefits of group therapy: Gains in social competence, self-confidence, self-reflection, interpersonal dynamics, and optimism/universality [14]. In several study, it was found that therapy in emotional adjustment and emotion regulation reduces the self-harming acts and improves the regulation of both negative and positive emotions in people, especially adolescents who are exposed to multiple negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Misst man die Wirksamkeit von CBASP nicht an der Reduktion der depressiven Kernsymptome, sondern an der Reduktion der mit der Diagnose einhergehenden Funktionseinschränkungen, so lassen sich zum derzeitigen Stand der Forschung folgende Ergebnisse resümieren: ▪ Prälogisches Denken: Eine Verbesserung des präoperatorischen Denkens erwies sich in einer 8-wöchigen Beobachtungsstudie als der wichtigste Prädiktor für einen Erfolg von CBASP [3] Verhaltensweisen und eine Abnahme feindseligsubmissiver Verhaltensweisen im Therapieverlauf [37], die ebenfalls mit einer Reduktion der Kernsymptomatik in Verbindung gebracht werden konnte [38,39]. Darüber hinaus berichten Personen nach einer Behandlung mit CBASP über eine größere Zunahme sozialer Problemlösefertigkeiten als nach Supportiver Therapie [40] und nach Behavioral Activation [41].…”
Section: Reduktion Der Interpersonellen Funktionsdefiziteunclassified
“…In einer qualitativen Datenerhebung zur Wirksamkeit von Situationsanalysen im Gruppensetting gaben Patient*innen einen Zuwachs an Sozialkompetenz, ein vermehrtes Selbstbewusstsein, eine erhöhte Selbstreflektion und ein gestiegenes Verständnis für interpersonelle Beziehungsdynamiken an [39].…”
Section: Wirksamkeitunclassified